Peningkatan Nilai Sistem Pertanahan Pada Tower Transmisi SUTT 70 kV PLTMG Flores – Labuan Bajo - Satyo Prihutomo; Adisastra Pengalaman Tarigan; Hikmatul Fadhilah Sianipar (CV. Hawari, 2025)
The construction of the 70 kV SUTT Rangko - Labuan Bajo transmission line has faced challenges in the grounding work. According to SPLN T5.012_2020, there are specific grounding requirements for the tower structures and cable parts of SUTT towers. Flores Island has mountainous and hilly terrain, with several active volcanoes, which often results in high and fluctuating soil resistivity. Improving the grounding value at the SUTT 70 kV Rangko - Labuan Bajo towers to meet SPLN T5.012_2020 standards is essential for enhancing the reliability of electrical installations and systems in Flores. Routine maintenance of the grounding system is necessary because it is crucial for protecting tower components, especially during lightning strikes. For the tower grounding improvement, the counterpoise method was used. Initial measurements showed that the grounding resistance at four tower points did not meet the required standard. This paper discusses improving the grounding value at these four towers using the counterpoise method, namely by adding stick rods to each tower leg until the required standard value is met (≤ 3 Ω for the five towers near the substation and a maximum of 10 Ω in other areas).